Varicella-Zoster virus seroprevalence in healthcare workers in Kuala Lumpur, Malaysia - Sam, I.C.; Tariman, H.; Chan, Y.F.; Bador, M.K.; Yusof, M.Y.M.; Hassan, Hamimah (Malaysian Medical Association, 2008)
Varicella-zoster virus (VZV) infections are a particular problem in healthcare settings. A survey of chickenpox was carried out amongst healthcare workers (HCWs) following potential ward exposures. A prior history of chickenpox was given by 61/98 (62.2). Of 64 HCWs tested for VZV IgG, 10 (15.6) were seronegative, indicating susceptibility. The sensitivity, specificity, positive predictive value, and negative predictive value of a history of prior chickenpox were 57.4, 90, 96.4, and 31.0, respectively. VZV screening of HCWs without a history of chickenpox, and vaccination of susceptible HCWs should be undertaken in this hospital.